Մեծ Եղեռնի տարիներին հայ մանուկների նկատմամբ կիրառված բռնությունները - Հմայակ Հարությունյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Пожалуй, одним из самых болезненных вопросов геноцида являются раз ные уголовные насилия над армянскими маленькими детьми, которые с точки зрения международного права расматриваются как форма проявления геноцида и соответствуют 4 и 5 пунктам 2-й статьи резолюции ООН от 9-ого декабря 1948 г. However, in the science that studies Genocide the most painful core problems are the different types of criminal violence applied to Armenian young children, those violence are observed as a way of genocide demonstration from the point of view of international Law and correspond to the United Nations Convention on 9 December 1948 Article 2 points 4 and 5.
Keywords: History; Armenian Genocide (1915)